EFEKTIVITAS STRATEGI BAURAN PEMASARAN TERHADAP DAYA SAING PRODUK BONEKA: Studi Kasus pada Sentra Industri Boneka Sukamulya Bandung - TIRIS SUDRARTONO (Coopetition : Jurnal Ilmiah Manajemen, 2019)
This study aims to determine the effectiveness of the Marketing Mix Strategy on Product Competitiveness. In this research, the results show that the Product Strategy, Price Strategy, Distribution Strategy and Promotion Strategy if implemented well, the Product Competitiveness will experience a significant increase. The resulting product model must be in accordance with market desires, the product brand must be easily read and remembered by consumers, the size of the product is made standard by including on the Production Brand, Providing raw materials that are always available at competitive prices and quality and Choosing the right media in product promotion so the strategy used can be more effective in increasing product competitiveness.